SKIN NECROSIS FOLLOWING AESTHETIC PROCEDURES: MECHANISMS, PREVENTION, AND MANAGEMENT STRATEGIES - Karolina Zygoń-Komendarczyk; Aleksandra Kwiatkowska; Dominik Woźniak; Mikołaj Dubiel; Sylwia Sanakiewicz; Patryk Obajtek (International Journal of Innovative Technologies in Social Science, 2026)
The growing global demand for minimally invasive aesthetic procedures has reshaped contemporary dermatologic and aesthetic practice. Although generally considered safe, these treatments carry a small but potentially severe risk of vascular complications. Among them, skin necrosis represents one of the most serious adverse outcomes, potentially leading to permanent scarring, tissue loss, functional impairment, and psychological distress. While dermal filler injections are most frequently implicated, ischemic injury has also been reported following autologous fat grafting, thread lifting, energy-based procedures, and deep chemical peels. This narrative review provides a clinical overview of the pathophysiology, risk factors, clinical presentation, prevention, and management of skin necrosis associated with aesthetic procedures. A literature search was conducted in PubMed, Scopus, and Web of Science for English-language publications between January 2015 and January 2025, focusing on vascular compromise and ischemic complications in aesthetic medicine. Current evidence indicates that intravascular injection and external vascular compression are the primary mechanisms leading to tissue ischemia. Early recognition of warning signs—including sudden blanching, severe pain, and livedoid discoloration—is essential, as delayed intervention increases the risk of irreversible damage. Management depends on the causative procedure, with hyaluronidase playing a central role in hyaluronic acid–related complications. Prevention relies on anatomical expertise, cautious injection techniques, and structured clinical preparedness, while standardized treatment algorithms and improved complication reporting remain essential for enhancing patient safety in modern aesthetic practice.